Chemoradiation for elderly patients (≥ 65 years) with esophageal cancer: a retrospective single-center analysis - Philipp Linde; Markus Mallmann; Anne Adams; Simone Wegen; Johannes Rosenbrock; Maike Trommer; Simone Marnitz; Christian Baues; Eren Celik (Radiation Oncology, 2022)
Abstract Background Present studies on the efficacy and safety of curative chemoradiation therapy (CRT) with esophageal cancer reflect heterogenous results especially in elderly patients. The aim of this study was to evaluate the toxicity and efficacy of CRT in patients ≥ 65 years. In a cohort, the focus centered around treatment-related toxicity (CTCAE Grade > 3), overall survival as well as progression free survival, comparing these rates in-between patients older than 70 years to those younger than 70 years. Methods A total of 67 patients older than 65 years (34 (50.7%) were older than 70 years) met the inclusion criteria for retrospective analysis (period from January 2013 to October 2017). Treatment consisted of radiotherapy and chemotherapy with carboplatin/paclitaxel or fluorouracil (5-FU)/cisplatin with the intention of neoadjuvant or definite chemoradiation. A sum of 67 patients received CRT (44 (65.6%) patients in neoadjuvant, 23 (34.4%) in definite intent). Of these, 22 and 12 patients were older than 70 years (50% and 52.2% in both treatment groups, respectively). Median age was 71 years and patients had a good physical performance status (ECOG 0: 57.6%, ECOG 1: 27.3%). Median follow-up was 24 months. Most patients had advanced tumour stages (T3 stage: n = 51, 79.7%) and nodal metastasis (N1 stage: n = 54, 88.5%). A subgroup comparison was conducted between patients aged ≤ 70 years and > 70 years. Results In severe (CTCAE Grade 3–5) toxicities (acute and late), no significant differences were observed between both patient groups (< 70 years vs. > 70 years). 21% had acute grade 3 events, 4 patients (4%) had grade 4 events, and two patients (3%) had one grade 5 event. Late toxicity after CRT was grade 1 in 13 patients (22%), grade 2 in two (3%), grade 3 in two (3%), grade 4 in four (7%), and grade 5 in one (2%). Median overall survival (OS) of all patients was 30 months and median progression-free survival (PFS) was 16 months. No significant differences were seen for OS (32 months vs. 25 months; p = 0.632) and PFS (16 months vs. 12 months; p = 0.696) between older patients treated with curative intent and younger ones. Trimodal therapy significantly prolonged both OS and PFS (p = 0.005; p = 0.018), regardless of age. Conclusion CRT in elderly patients (≥ 65 years) with esophageal cancer is feasible and effective. Numbers for acute and late toxicities can be compared to cohorts of younger patients (< 65 years) with EC who received the same therapies. Age at treatment initiation alone should not be the determining factor. Instead, functional status, risk of treatment-related morbidities, life expectancy and patient´s preferences should factor into the choice of therapy.